Lessons for Sustainable Science Education: A Study on Chemists' Use of Systems Thinking across Ecological, Economic, and Social Domains - Emmi Vuorio; Johannes Pernaa; Maija Aksela (MDPI AG, 2024)
This paper explores how concept maps can be structured based on researcher narration as a systems thinking (ST) approach in science education to portray the systemic nature of developmental work by chemists on solutions related to sustainability. Sustainability cannot be achieved without a systemic approach that considers all the domains of prosperity and well-being-ecological, social, and economic. Science education must respond to this challenge accordingly and find effective ways to include the ST approach. Data were collected from three semi-structured, in-depth interviews with chemists. The analysis was carried out using qualitative content analysis and modelling the systemic structures in concept maps as articulated by the chemists. The results show that authentic narratives of chemists' developmental work can be used as material in a concept mapping exercise to reveal several ST elements and learning objectives, including leverage points and delays, that have not been presented in previous exercises. The chemists' descriptions were also found to address the challenge of sustainability education by depicting a holistic and multidimensional picture of the reality where the developmental work is conducted. Furthermore, all three domains of sustainability were identified. The economic and industrial perspectives were especially valuable from the science education viewpoint.